Clinical Insights Into Heritable Cardiomyopathies - Martinez, Hugo R.; Beasley, Gary S.; Miller, Noah; Goldberg, Jason F.; Jefferies, John L. (Frontiers in Genetics, 2021)
Cardiomyopathies (CMs) encompass a heterogeneous group of structural and functional abnormalities of the myocardium. The phenotypic characteristics of these myocardial diseases range from silent to symptomatic heart failure, to sudden cardiac death due to malignant tachycardias. These diseases represent a leading cause of cardiovascular morbidity, cardiac transplantation, and death. Since the discovery of the first locus associated with hypertrophic cardiomyopathy 30 years ago, multiple loci and molecular mechanisms have been associated with these cardiomyopathy phenotypes. Conversely, the disparity between the ever-growing landscape of cardiovascular genetics and the lack of awareness in this field noticeably demonstrates the necessity to update training curricula and educational pathways. This review summarizes the current understanding of heritable CMs, including the most common pathogenic gene variants associated with the morpho-functional types of cardiomyopathies: dilated, hypertrophic, arrhythmogenic, non-compaction, and restrictive. Increased understanding of the genetic/phenotypic associations of these heritable diseases would facilitate risk stratification to leveraging appropriate surveillance and management, and it would additionally provide identification of family members at risk of avoidable cardiovascular morbidity and mortality.